Marginalisasi Petani dalam Bayang-Bayang Korporasi: Analisis Sosiologis atas Kepemilikan Tanah yang Tidak Berimbang: The Marginalization of Farmers in the Shadow of Corporations: A Sociological Analysis of Unequal Land Ownership - komarudin , komarudin (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2025)
Land ownership inequality has become a significant issue in Indonesia, particularly in South Sumatra, where large-scale corporations dominate vast agricultural areas while smallholder farmers struggle to secure their land rights. This study examines the marginalization of farmers within the framework of sociological theories, including structural inequality and power relations, to understand how corporate dominance over land impacts rural communities. Using a qualitative approach, this research analyzes the socio-economic conditions of smallholder farmers, their challenges in accessing land, and the resulting conflicts with corporate entities and the state. The findings reveal that land tenure insecurity forces many farmers into exploitative labor conditions, limiting their economic independence and reinforcing social stratification. Additionally, the government's agrarian policies often favor large-scale agribusinesses, further deepening rural inequality. To address these issues, policy recommendations include agrarian reform, legal land protection for small farmers, and strengthening farmer cooperatives as a means of economic empowerment. This study contributes to the discourse on land justice and sustainable rural development in Indonesia.